Sultan Hasanuddin dan Arung Palakka Abad XVII: Berpikir Historis, Menempatkan Pada Tempatnya - A. Malik Fajar; Bahri Bahri (IAIN Syekh Nurjati Cirebon, 2023)
This paper discusses Sultan Hasanuddin and Arung Palakka in the power constellation in South Sulawesi. This paper aims to discuss the position and heroism of the figures Sultan Hasanuddin and Arung Palakka using a historical approach with the ultimate goal of being able to place these two figures in their place. This study uses the historical method, known as four stages, namely gathering sources, analyzing the literature in the library, interpreting the data found, and writing history (historiography). Research shows that understanding the position of Sultan Hasanuddin and Arung Palakka needs to be seen from many aspects. Sultan Hasanuddin is a political historical figure who must be received with pride. Sultan Hasanuddin is in a macro unit in political history. His name is beautifully engraved on the surface of political history in Indonesia. Elsewhere, there is a prominent figure, Arung Palakka, who is in a micro (social) unit, his name is embedded deep in the hearts of the people and is firmly positioned in social history. To understand the actions of these two figures, it is necessary to use a historical approach, namely in understanding history, it is necessary to study historical sources and have a broad spatial scope.